SGS-LTER disturbance intensity and above- and belowground herbivory effects on long-term recovery of shortgrass steppe on the Central Plains Experimental Range, Nunn, Colorado, USA 1977-1990 - Lauenroth, William K. (Colorado State University. Libraries, 1977)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. The importance of disturbance intensity and herbivory by cattle and white grubs, or the larvae of June beetles to recovery of shortgrass steppe ecosystems in Colorado, USA were evaluated over a 14 year time period. Disturbance intensity was defined by survival of the dominant grass species (Bouteloua gracilis) after an outbreak of root feeding activity by white grubs. 16 patches of vegetation consisting of four pairs of adjacent ungrazed-grazed by cattle locations with 2 replicates that were recently affected by white grubs were selected in 1977. Disturbance intensity was determined in 1977 by the area in each patch that contained live tillers of B. gracilis. Permanent plots were located both within and outside of each patch. Plant basal cover and density by species were estimated at time of peak aboveground biomass in 6 different years on each plot. Successional dynamics on patches was similar to areas affected by other types of disturbances, however, rate of recovery was faster for patches affected by grubs. Grazing by cattle was infrequently important to plant recovery, a result similar to effects of grazing on other aspects of shortgrass steppe. Disturbance intensity was important to recovery of B. gracilis since tiller survival in 1977 was linearly related to cover in each year of sampling. For ungrazed patches, initial conditions were important to recovery of B. gracilis for as many as 14 years. For grazed patches, initial conditions decreased and grazing increased in importance through time. Changes in resource quality and more uniform distribution of roots due to grazing likely resulted in more complete mortality of plants by grubs under grazed compared to ungrazed conditions. Persistence of shortgrass steppe ecosystems in spite of disturbances with different intensities are determined at least in part by characteristics of disturbances interacting with the ability of plants to respond, and in part by the evolutionary history of the system. Although white grubs affect shortgrass communities infrequently, they have large and important effects on plant community structure through time, and represent an important class of disturbance defined by intensity.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: disturbance; cover; density; biomass; grasslands; invertebrates; plant/animal interactions; plants; succession; populations; blue grama